(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
An overwhelming scientific consensus confronts us with the need to radically transform our habits to cope with the climate crisis in which we are living. The production of data – in addition to the re- lated flow of information and images regarding the threat to our survival and ecosystems – is not enough to activate our pro-environment actions. To set radical change in motion, it is necessary to design imaginative interventions based on the knowledge gained in embodied cognitive science so that interventions are directed not at disembodied minds but at situated indi- viduals enacting within a rich landscape of affordances. By way of experimenting with philosophy through unorthodox means, I will present a concrete artwork, Infinity Pool, whose purpose is to enact tangible invitations addressed to a situated community through a monstrous education of attention, that is, through an imaginative invitation that offers an opportunity to bring attention to aspects of the environ- ment usually ignored.